Hanging towers, or setting on crisis compression (ARQUISUR Revista, 2020)
We can understand the modern architecture, product of the industrial revolution in the West, as the transfer of a mono-material way of building, where the thermal, stagnant and stable functions of the envelope are reduced to a single material, which through its thickness solves all the problems related to comfort; to the construction of the differentiation of the envelopes where each layer will fulfill a specific function with the lowest possible thickness and weight. Within this scheme the supporting structure, from the development of materials that work very well to traction (iron and reinforced concrete), goes from being a continuous structure, such as the wall and the vault, to be a system of elements articulated. In this context we can define it as a change of constructive paradigm from stereotomic construction to tectonic construction. In this context we could think that this reduction of the structural material to the minimum section, reaches its maximum expression in the towers of suspended structures, in the minimum section of its cables working with traction, could we define this process, in broad terms, as a put in crisis of compression?
Keywords: architecture, project, technology towers, hanging towers, light construction